RECQL5 plays an essential role in maintaining genome stability and viability of triple‐negative breast cancer cells. (23rd June 2019) - Peng, Jin; Tang, Lichun; Cai, Mengjiao; Chen, Huan; Wong, Jiemin; Zhang, Pumin
Abstract: Triple‐negative breast cancer (TNBC) is a malignancy that currently lacks targeted therapies. The majority of TNBCs can be characterized as basal‐like and has an expression profile enriched with genes involved in DNA damage repair and checkpoint response. Here, we report that TNBC cells are under replication stress and are constantly generating DNA double‐strand breaks, which is not seen in non‐TNBC cells. Consequently, we found that RECQL5, which encodes a RecQ family DNA helicase involved in many aspects of DNA metabolism including replication and repair, was essential for TNBC cells to survive and proliferate in vitro and in vivo. Compromising RECQL5 function in TNBC cells results in persistence of DNA damage, G2 arrest, and ultimately, cessation of proliferation. Our results suggest RECQL5 may be a potential therapeutic target for TNBC. Abstract : The high levels of endogenous DNA damage in triple‐negative breast cancer (TNBC) cells make RECQL5 essential, and therefore a potential drug target against TNBC.